1997
DOI: 10.1083/jcb.139.5.1089
|View full text |Cite
|
Sign up to set email alerts
|

The Human DnaJ Homologue dj2 Facilitates Mitochondrial Protein Import and Luciferase Refolding

Abstract: DnaJ homologues function in cooperation with hsp70 family members in various cellular processes including intracellular protein trafficking and folding. Three human DnaJ homologues present in the cytosol have been identified: dj1 (hsp40/hdj-1), dj2 (HSDJ/hdj-2), and neuronal tissue-specific hsj1. dj1 is thought to be engaged in folding of nascent polypeptides, whereas functions of the other DnaJ homologues remain to be elucidated. To investigate roles of dj2 and dj1, we developed a system of chaperone depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 47 publications
4
103
0
Order By: Relevance
“…Importantly, addition of the general ER chaperone BiP did not restore the activity of heat-denatured T-synthase, whereas BiP does support renaturation of luciferase. It has been shown previously that recombinant Hsc70 can support in vitro refolding of heat-denatured luciferase (38). Furthermore, 6ϫHis-msCosmc E152K cannot restore the denatured HPC4-sT-syn in vitro as efficiently as 6ϫHis-sCosmc and 6ϫHis-sCosmc does not effect restoration of activity for another well-characterized ␤-galactosyltransferase (␤4-GalT).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, addition of the general ER chaperone BiP did not restore the activity of heat-denatured T-synthase, whereas BiP does support renaturation of luciferase. It has been shown previously that recombinant Hsc70 can support in vitro refolding of heat-denatured luciferase (38). Furthermore, 6ϫHis-msCosmc E152K cannot restore the denatured HPC4-sT-syn in vitro as efficiently as 6ϫHis-sCosmc and 6ϫHis-sCosmc does not effect restoration of activity for another well-characterized ␤-galactosyltransferase (␤4-GalT).…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal anti-human dj1 and dj2 antibodies were those described elsewhere. 28 Monoclonal antibody against mouse iNOS was obtained from Transduction Laboratories (Lexington, KY, USA). A polyclonal antibody against mouse CHOP and polyclonal and monoclonal antibodies against human Bax were obtained from Santa Cruz Biotechnology Inc. Polyclonal antibody against GFP was as described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 Several mammalian DnaJ homologs (hsp40 family members) have been identified, 27 and it seems likely that hsp70 family members are regulated by these homologs. 28 Major DnaJ homologs in mammalian cytosol are dj1 (DNAJB1: hsp40/ hdj-1) and dj2 (DNAJA1: HSDJ/hdj-2). We reported that dj1-hsp70 and dj2-hsp70 chaperone pairs are both effective in preventing NO-mediated apoptosis upstream of both caspase 3 activation and cytochrome c release from the mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…A polypeptide substrate commonly used to study Hsc70 function is firefly luciferase, which has a sensitive and reproducible enzymatic assay. Purified Hsc70 has been shown to assist luciferase refolding in numerous studies (Hohfeld et al, 1995;Minami et al, 1996;Hohfeld and Jentsch, 1997;Terada et al, 1997;Luders et al, 2000;Terada and Mori, 2000). However, in most cases the stress-inducible cochaperone Hsp40 was used, and a direct comparison between all three DJAs with Hsc70 has not yet been reported.…”
Section: Dja Activation Of Hsc70mentioning
confidence: 99%